Oxidative Stress in Autism Spectrum Disorder - Bjørklund, Geir; Meguid, Nagwa A; El-Bana, Mona A; Tinkov, Alexey A; Saad, Khaled; Dadar, Maryam; Hemimi, Maha; Skalny, Anatoly V; Hosnedlová, Božena; Kizek, Rene; Osredkar, Joško; Urbina, Mauricio A; et al. (Molecular neurobiology, 2020)
According to the United States Centers for Disease Control and Prevention (CDC), as of July 11, 2016, the reported average incidence of children diagnosed with an autism spectrum disorder (ASD) was 1 in 68 (1.46%) among 8-year-old children born in 2004 and living within the 11 monitoring sites' surveillance areas in the United States of America (USA) in 2012. ASD is a multifaceted neurodevelopmental disorder that is also considered a hidden disability, as, for the most part; there are no apparent morphological differences between children with ASD and typically developing children. ASD is diagnosed based upon a triad of features including impairment in socialization, impairment in language, and repetitive and stereotypic behaviors. The increasing incidence of ASD in the pediatric population and the lack of successful curative therapies make ASD one of the most challenging disorders for medicine. ASD neurobiology is thought to be associated with oxidative stress, as shown by increased levels of reactive oxygen species and increased lipid peroxidation, as well as an increase in other indicators of oxidative stress. Children with ASD diagnosis are considered more vulnerable to oxidative stress because of their imbalance in intracellular and extracellular glutathione levels and decreased glutathione reserve capacity. Several studies have suggested that the redox imbalance and oxidative stress are integral parts of ASD pathophysiology. As such, early assessment and treatment of antioxidant status may result in a better prognosis as it could decrease the oxidative stress in the brain before it can induce more irreversible brain damage. In this review, many aspects of the role of oxidative stress in ASD are discussed, taking into account that the process of oxidative stress may be a target for therapeutic interventions.
Keywords: Mitochondria; poruchy autistického spektra; Gastrointestinal Microbiome; Oxidative Stress; selen; oxidační stres; Humans; neurodegenerativní nemoci; dítě; Oxidative stress; centrální nervový systém; aerobióza; Aerobiosis; Child; Glutathione Peroxidase; oxidace-redukce; Autism Spectrum Disorder; Reactive oxygen species; peroxidace lipidů; Inflammation; lidé; mitochondrie; gastrointestinální nemoci; Antioxidants; glutathionperoxidasa; dysbióza; Metallothionein; scavengery volných radikálů; Selenium; Free Radical Scavengers; Brain Chemistry; předškolní dítě; antioxidancia; mozek - chemie; Dysbiosis; incidence; Incidence; ASD; Autism; Central Nervous System; Oxidation-Reduction; Neurodegenerative Diseases; střevní mikroflóra; metalothionein; selenoproteiny; Child, Preschool; Gastrointestinal Diseases; Lipid Peroxidation; Selenoproteins